Treatment of Multiple Sclerosis with Cladribine Tablets: Literature Review and the Guidance of the Lithuanian Association of Neurologists - R. Kizlaitienė; D. Mickevičienė; L. Malcienė; N. Giedraitienė; R. Balnytė; D. Jatužis (Neurologijos seminarai)
Cladribine is a disease-modifying drug used for the treatment of the highly active relapsing-remitting form of multiple sclerosis. Cladribine is a purine nucleoside analogue which selectively targets lymphocyte subpopulations involved in the pathogenesis of multiple sclerosis, and therefore it is classified as an immune reconstitution therapy drug. Two short courses of cladribine tablets given over two years significantly reduce the multiple sclerosis relapse rate and disability progression. For most patients, the effect persists in the third and the fourth year. This makes cladribine convenient for patients with multiple comorbidities, difficulties in adhering to their prescribed treatment regimen, those planning a pregnancy, or those for whom long-term immunosuppression is undesirable. Cladribine tablets are denoted by good safety characteristics, with the most prominent adverse effect being lymphopenia, which does not lead to an increased risk of infections other than Herpes zoster. However, in clinical practice, there are a number of issues related both to the initial administration of cladribine tablets and the strategy of treatment in different clinical situations during the first-to-fourth years of treatment, and particularly after the fourth year. Although there are no contraindications for additional courses of cladribine tablets, the product information does not provide detailed guidance on their continued use. During more than five years after the approval of the medicinal product, the new clinical trial data and the Real-World Evidence (RWE) on the efficacy and safety of cladribine tablets have become available, based on which, several national and international expert panels, as well as the Lithuanian Association of Neurologists, have issued guidance on the use of cladribine tablets reviewed in this article. Upon reactivation of the disease, additional courses of cladribine tablets or other disease-modifying therapies may be prescribed, depending on various factors related to the severity of the relapse, patient characteristics, and previously used medications. If the patient’s condition remains stable after the fourth year, extension of the treatment-free period with the structured monitoring approach could be appropriate.